The Influence of Organizational Communication, Participative Leadership, and Work Motivation on Employee Creativity: Case Study in the Creative Industries in Bali - Mayasari, Nanny; Suhara, Ade; Marlita, Devi; Widowati, Retno; Damiyana , Damdam (The Eastasouth Management and Business, 2024)
This research examines the relationship between organizational communication, participative leadership, work motivation, and employee creativity in the creative industries in Bali. A quantitative research design was adopted, and data was collected from 128 employees working in various creative sectors. Structural Equation Modeling (SEM-PLS) was used for data analysis. The research results show a significant positive relationship between organizational communication, participative leadership, work motivation and employee creativity. Organizational communication, participative leadership, and work motivation together explain about 60.2% of the variance in employee creativity. These findings underscore the importance of fostering open communication channels, empowering leadership practices, and motivational strategies to foster a culture of creativity and innovation in Bali's creative industries. Despite the contributions of this study, several limitations must be acknowledged, the cross-sectional nature of the data limits causal conclusions about the relationships studied.